Analyzing the Use of Flipped Classroom through Students’ Learning Environment: A Perspective from EFL Learners - Ananda, Salsabila Auliya; Ratri, Devinta Puspita (Universitas Pahlawan Tuanku Tambusai, 2024)
Learning innovation is one of the important things in the development of student learning process and experience, one of them is Flipped Classroom. It is one of teaching innovation and methodology that is still actively utilize by the educators nowadays. Therefore, this research is to analyze students' perspective about the use of flipped classroom through their learning environment. The research methodology used is a quantitative survey design. This research involved 100 fifth and seventh semester students majoring in English Language Education at Universitas Brawijaya. These students have experienced using the flipped classroom in their learning. A close-ended questionnaire via Google Form was used to collect data from the participants about the efficacy and challenges in using a flipped classroom through their environment. The data of this research were analyzed through descriptive statistics. Focused on the results, despite recent research indicates that some students find it difficult to concentrate outside of the classroom due to interruptions or distractions. most of students give their positive perspective toward the use of flipped classroom, as demonstrated by its effectiveness in assisting with offline session preparation and increasing their level of participations.